Investigation of Antioxidant Capacity and Some Bioactive Compounds of Iranian Pistachio (Pistachio vera L.) Cultivars - Gholamhossein DAVARYNEJAD; Éva STEFANOVITS-BÁNYAI; Peter Tamas NAGY (Notulae Scientia Biologicae, 2012)
Edible nuts have an increasing role in human diet. Pistachio is a popular but less known kind of edible nut nevertheless it is rich in health benefiting nutrients, minerals, antioxidants and vitamins. Therefore, this study attempts to determine the antioxidants capacity, total phenolics and amount of some major elements (nitrogen, potassium, calcium and phosphorus), present in the most important Iranian pistachio nut, to enhance the health benefits, and use in breeding programs. For this reason eleven pistachio cultivars (‘Akbary’, ‘Ahmad Aghaii’, ‘Daneshmandi’, ‘Kalle Ghoochi 1’, ‘Kalle Ghoochi 2’, ‘Garmeh’, ‘Ohadi 1’, ‘Ohadi 2’, ‘Sefid’, ‘Momtaz’, and chance seedling tree ("None-grafted") as control) which are grown in commercial orchards of Fayzabad (Khorasan-e-Razavi) were analyzed for determination of some major elements, antioxidants capacity and total phenolics contents. The results showed that the amounts of the nutrients in 100 g kernel were within the following ranges: N 2.5-4.1 g, P 355.9-546.6 mg, K 573.6-994.9 mg and Ca 61.5-134.5 mg. Total phenolics content varied from 5.3-9.9 mg gallic acid equivalents in g fresh weight. The results also showed that the capacity of antioxidant ranged from 1.6-3.7 (mg ascorbic acid equivalents in g fresh weight). Weak correlation was observed between total phenolic content and total antioxidant capacity (r2=0.3824). The result demonstrates that there is adequate variation in major elements, antioxidants capacity and total phenolics contents within pistachio cultivars and hence there is potential for improvement towards enhancing these health-promoting photochemical in this nuts.